Methods of melanoma detection and of skin monitoring for individuals at high risk of melanoma: new Australian clinical practice. Issue 1 (2nd December 2018) - Adler, Nikki R; Kelly, John W; Guitera, Pascale; Menzies, Scott W; Chamberlain, Alex J; Fishburn, Paul; Button‐Sloan, Alison E; Heal, Clinton; Soyer, H Peter; Thompson, John F
Abstract: Introduction: The evidence‐based national clinical practice guidelines for the management of cutaneous melanoma published in 2008 are currently being updated. This article summarises the findings from multiple chapters of the guidelines on different methods of melanoma detection and of monitoring the skin for patients at high risk of melanoma. Early detection of melanoma is critical, as thinner tumours are associated with enhanced survival; therefore, strategies to improve early detection are important to reduce melanoma‐related mortality. Main recommendations: Clinicians who perform skin examinations for the purpose of detecting skin cancer should be trained in and use dermoscopy. The use of short term sequential digital dermoscopy imaging to detect melanomas that lack dermoscopic features of melanoma is recommended to assess individual melanocytic lesions of concern. The use of long term sequential digital dermoscopy imaging to detect melanomas that lack dermoscopic features of melanoma is recommended to assess individual or multiple melanocytic lesions for routine surveillance of high risk patients. The use of total body photography should be considered in managing patients at increased risk for melanoma, particularly those with high naevus counts and dysplastic naevi. There is insufficient evidence to recommend the routine use of automated instruments for the clinical diagnosis of primary melanoma. Management overview: Determining the relative indications for each diagnostic method and how each method should be introduced into the surveillance of a patient requires careful consideration and an individualised approach.